Sobre la entropía del español escrito - Guerrero, Fabio G. (Revista Colombiana de Estadística, 2012)
A discussion on the entropy of the Spanish language by means of a practicalmethod for calculating the entropy of a text by direct computer processingis presented. As an example of application, thirty samples of Spanish textare analyzed, totaling 22.8 million characters. Symbol lengths from n = 1 to500 were considered for both words and characters. Both direct computerprocessing and the probability law of large numbers were employed for calculatingthe probability distribution of the symbols. An empirical relationon entropy involving the length of the text (in characters) and the number ofdifferent words in the text is presented. Statistical properties of the Spanishlanguage when viewed as produced by a stochastic source, (such as originshift invariance, ergodicity and asymptotic equipartition property) are alsoanalyzed.